CORONAVIRUS-RELATED ANXIETY WITH HYPERGLYCEMIA IN TYPE 2 DIABETES PATIENTS - Kholisotul Hikmah; Helda Helda; Caroline Killeen (Jurnal Berkala Epidemiologi, 2022)
Background: COVID-19 might also predispose individuals to elevate blood glucose as the effect of anxiety. Blood glucose level is an important risk factor for the prognosis of disease among diabetes patients.  Purpose: This study aimed to assess the effect of Coronavirus-related anxiety with hyperglycemia incidence among type 2 diabetes patients. Methods: A cross-sectional study was conducted among 143 individuals with type 2 diabetes mellitus, from 25 January to 29 February 2021. This study was conducted both online and by assessing archives of medical records using random samples.  Results: A total of 143 respondents completed the questionnaire, with 59.44% females and 40.56% males. More than half of the respondents (55.94%) who reported hyperglycemia showed COVID-19 anxiety, and 51.05% of them experienced ≥ 8 years of diabetes. COVID-19 anxiety was associated positively with the risk of hyperglycemia among type 2 diabetes patients (PR>1). Severe worry about the pandemic had the highest risk of hyperglycemia compared to moderate and mild anxiety. This finding is confounded by diabetes duration (PR discrepancy >10% and PR>1 for ≥8 years long-duration). Conclusion: This study suggests a positive association between COVID-19 anxiety and hyperglycemia while the degree of anxiety is associated with an increased risk of hyperglycemia.